Evaluation of a telehealth psychological support intervention for people with primary brain tumour and their family members: Study protocol for a randomised controlled trial. (10th July 2019) - Ownsworth, Tamara; Chambers, Suzanne; Aitken, Joanne F.; Foote, Matthew; Pinkham, Mark B.; Gordon, Louisa G.; Lock, Gemma; Hanley, Brigid; Gardner, Tracey; Jones, Stephanie; Robertson, Julia; Shum, David; et al.
Abstract: Objective: There is a lack of research on interventions that address the specific psychosocial needs of people with brain tumour and their families. This paper describes the protocol for a pragmatic randomised control trial (RCT) evaluating the clinical efficacy and cost‐effectiveness of the Making Sense of Brain Tumour program delivered via telehealth (Tele‐MAST) relative to standard care. Methods: The 148 adults with primary brain tumour will be randomly allocated to the 10‐session Tele‐MAST videoconferencing program or standard care from a cancer counselling service. The primary outcome is level of depression and secondary outcomes are quality of life, mental health and incremental cost per quality‐adjusted life year. The mental health and quality of life of family members will also be assessed. Assessments will be conducted at pre‐intervention, post‐intervention (primary endpoint), 6‐weeks post‐intervention and 6‐months post‐intervention. The main analysis will determine whether the Tele‐MAST intervention is more effective than standard care at post‐intervention, and whether these effects are sustained at follow‐up. Conclusion: Results will indicate whether the Tele‐MAST program is associated with better clinical outcomes and is more cost‐effective than existing cancer support services. Such outcomes will contribute to effective and accessible psychosocial care for the brain tumour population.